Dampak Pengembangan Kebijakan City Branding “Ngawi Ramah” terhadap Realisasi Investasi di Kabupaten Ngawi - Anwar, Khoyrul; Mala, Istiana Wijayanti (Publikasi Penelitian Terapan dan Kebijakan, 2023)
Ngawi Regency implemented a city branding policy through the slogan "Ngawi Ramah" which initially only aimed to increase tourist visits. Then the policy was developed again to attract and bring investment. The strategy taken is to offer various conveniences for investors, especially in terms of business license management services. This study aims to determine how the impact of city branding policy on investment realization achievements. This study used a qualitative descriptive approach. Data collection was conducted through interviews and document review. Data analysis is carried out interactively through stages: data collection, assessment, interpretation, and conclusion. The results showed that the development of the "Ngawi Ramah" city branding policy through various service innovations offered has succeeded in attracting investors to invest, so that it has an impact on achieving investment realization performance which tends to increase every year. This policy is considered to have been able to increase investment realization, however, all levels of work units in Ngawi Regency still need to continue to carry out stronger, massive and widespread marketing, and also increased commitment and creativity in developing various programs so that city branding policies are increasingly realized and can better sell the potential of Ngawi Regency.